PLANEJAMENTO DE ENTREGAS EM ÁREAS URBANAS CONSIDERANDO RECARREGAMENTO INTERMEDIÁRIO, VEÍCULOS COM MÚLTIPLOS COMPARTIMENTOS, MÚLTIPLOS DEPÓSITOS E RESTRIÇÃO DE ACESSO - Astoures, Henrique Fiorot (2021)
In a recent period, there has been an increase in the demand for the transportation of goods by businesses and homes in large urban centers, especially in periods like Corona virus pandemic, imposing the increased demand for vehicles to carry out these transports. With the socioenvironmental impacts inherent to this growth, city authorities deemed it necessary to restrict delivery by large vehicles, making it necessary to prepare an urban logistics plan in these large centers. Thus, this dissertation proposes a new class of problem called Site-Dependent Multi-Depot Compartment Vehicle Routing Problem with Intermediate Replenishment Facilities and Time Windows to solve the problem of deliveries in urban areas with heavy traffic and legislation restricting the entry of large vehicles, considering the planning of urban logistics for the last mile delivery. The goal is minimizing the total cost of deliveries in urban areas considering multiple warehouses, unit allocation of boxes in multiple compartments, site dependent, customer service and intermediate facilities time window, and intermediate facilities for refueling. The mathematical model was tested in the CPLEX 12.8 software in instances generated from preliminary data from a company that is studying the economic and operational feasibility in the city of Vitória, Espírito Santo. A mathematical model that meets the studied problem was presented, incorporating real operational characteristics, and the results of the tests performed showed that, for the tested instances, having more intermediate warehouses available is the most economical strategy.